Positive Definite Matrices - Bhatia, Rajendra, 1952- (Book collections on Project MUSE., 2007)
This book represents the first synthesis of the considerable body of new research into positive definite matrices. These matrices play the same role in noncommutative analysis as positive real numbers do in classical analysis. They have theoretical and co.